Research on the Impact of Fintech on Traditional Accounting Industry and Transformation Strategies - Bai, Xueying (Transactions on Economics, Business and Management Research, 2024)
Financial technology (FinTech) has developed rapidly in recent years, profoundly affecting the operation mode and business processes of the traditional accounting industry. This paper discusses the major impacts of FinTech on the traditional accounting industry, including the changes in accounting processes due to technological innovations, the application of data analytics and automation, and the security and privacy issues faced. As FinTech continues to advance, the traditional accounting industry needs to implement effective transformation strategies to meet the challenges and capitalize on the opportunities. This paper proposes four key transformation strategies: technology integration and upgrading, business process optimization and restructuring, cultivation and introduction of professionals, and compliance and security enhancement. Through the analysis of successful transformation cases, this paper summarizes the practical experience and looks forward to the trends and challenges of FinTech on the future development of the accounting industry. The study suggests that actively adapting to the changes in fintech is the key to maintaining the competitiveness and realizing the sustainable development of the traditional accounting industry.